Pemanfaatan Nangka Muda dalam Pembuatan Sup Krim dengan Teknik fusion - Tri Rettagung Diana; Deddy Mushthafainl Akhyar (Garina, 2021)
The use of young jackfruit which has low prices and abundant production is only as a basic ingredient for making traditional foods. Considering the benefits and nutritional content of young jackfruit, it is necessary to innovate the manufacture of young jackfruit cream soup with fusion techniques. The research objectives are 1) to know the process of making young jackfruit cream soup using fusion technique; 2) knowing the formula and thickening agent for young jackfruit cream soup; 3) find out the community's acceptance of young jackfruit soup cream. The experiment was carried out three times by making cream soup with 3 different thickeners, namely wheat flour with a roux system, pumpkin and potatoes. The experiment was carried out to obtain the best formula. The experimental results show how to make young jackfruit with fusion food processing techniques, starting with material selection, weighing ingredients, boiling young jackfruit, making spices, sauteing spices, boiling all ingredients, sorting bones, thickening with, wheat flour/ pumpkin/potatoes and blending. soup, filter soup. The right formula for young jackfruit cream soup is young jackfruit 120 g, pumpkin thickener 40 g(531)/roux flour 20 gr (351)/ potato 40 gr (253), 50 ml liquid milk, 2 g salt, 10 g onion, 4 g granulated sugar, 5 g margarine, 500 cc water and 140 g claws. The three experimental products were tested hedonic by 10 semi-trained people and code 531 was preferred because it has the characteristics of creamy soup with a creamy texture, savory taste, light brown color, and has the aroma of young jackfruit mixed with milk.